In vitro and in silico biopotentials of phytochemical compositions and antistaphylococcal and antipseudomonal activities of volatile compounds of Argania spinosa (L.) seed oil - Almuhayawi, Mohammed S.; Alruhaili, Mohammed H.; Gattan, Hattan S.; Alharbi, Mohanned Talal; Nagshabandi, Mohammed K.; Hagagy, Nashwa; Almuhayawi, Saad M.; Al Jaouni, Soad K.; Selim, Samy; Mostafa, Ehab M.; Elnosary, Mohamed E. (Frontiers in Bioengineering and Biotechnology, 2024)
Active components in medicinal plants provide unlimited useful and traditional medicines. Antimicrobial activities are found in secondary metabolites in plant extracts such as argan oil. This experimental investigation aims to determine argan oil’s volatile compounds and examine their in vitro antimicrobial properties. In silico simulations, molecular docking, pharmacokinetics, and drug-likeness prediction revealed the processes underlying the in vitro biological possessions. Gas chromatography–mass spectrometry (GC/MS) was used to screen argan oil’s primary components. In silico molecular docking studies were used to investigate the ability of the selected bioactive constituents of argan oil to act effectively against Pseudomonas aeruginosa and Staphylococcus aureus (S. aureus) isolated from infections. The goal was to study their ability to interact with both bacteria’s essential therapeutic target protein. The 21 chemicals in argan oil were identified by GC/MS. Docking results for all compounds with S. aureus and P. aeruginosa protease proteins ranged from −5 to −9.4 kcal/mol and −5.7 to −9.7 kcal/mol, respectively, compared to reference ligands. Our docking result indicates that the 10-octadecenoic acid, methyl ester was the most significant compound with affinity scores of −9.4 and −9.7 kcal/mol for S. aureus and P. aeruginosa proteins, respectively. The minimal bactericidal concentration (MBC) and minimal inhibitory concentration (MIC) of argan oil were 0.7 ± 0.03 and 0.5 ± 0.01 for S. aureus and 0.4 ± 0.01 and 0.3 ± 0.02 for P. aeruginosa, respectively. We confirmed the antimicrobial properties of argan oil that showed significant growth inhibition for S. aureus and P. aeruginosa.